Föderale Vielfalt - Globale Vernetzung. Digitalisierung in den Ländern und der Welt - Euler, Ellen; Klimpel, Paul (Kulturelles Erbe in der digitalen Welt, 2016)
The contributions in the second volume of the series "Cultural Heritage in the Digital World" published by the German Digital Library show how in Germany, with its federal order, the mediation and ultimate networking of the cultural heritage is made via the Internet. The contributions provide information on the organizational structure and the infrastructure of digitization and on cooperation and political conditions. They show the political agenda in relation to the actual achievements. Teh status of the implementation is described. The articles provide information about digitization sites, projects and their coordination, describe institutional responsibilities, portals and cooperation with the German Digital Library, contain comments on long-term archiving. An outlook closes the considerations. Examples of concepts outside Germany complete the picture.